The Routledge history of gender, war, and the U.S. military
1 online resource (xv, 363 pages)
Keywords: "The Routledge History of Gender, War, and the US Military is the first examination of the interdisciplinary, intersecting fields of gender studies and the history of the United States military. In twenty-one original essays, the contributors tackle themes including gendering the 'other', gender and war disability, gender and sexual violence, gender and American foreign relations, and veterans and soldiers in the public imagination, and lay out a chronological examination of gender and America's wars from the American Revolution to Iraq. This important collection is essential reading for all those interested in how the military has influenced America's views and experiences of gender. "--Provided by publisher.